2021
DOI: 10.3390/ijms221910844
|View full text |Cite
|
Sign up to set email alerts
|

Optical Fibre-Enabled Photoswitching for Localised Activation of an Anti-Cancer Therapeutic Drug

Abstract: Local activation of an anti-cancer drug when and where needed can improve selectivity and reduce undesirable side effects. Photoswitchable drugs can be selectively switched between active and inactive states by illumination with light; however, the clinical development of these drugs has been restricted by the difficulty in delivering light deep into tissue where needed. Optical fibres have great potential for light delivery in vivo, but their use in facilitating photoswitching in anti-cancer compounds has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Although it is not related to combretastatins, endoscope-assisted phototherapy was carried out using a photoswitchable proteasome inhibitor and HCT-116 human CRC cell line recently[ 69 ]. Thus, photopharmacology was achieved with a CRC cell line model system.…”
Section: Development Of Endoscopy Capable Of Handling Two-photon Illu...mentioning
confidence: 99%
“…Although it is not related to combretastatins, endoscope-assisted phototherapy was carried out using a photoswitchable proteasome inhibitor and HCT-116 human CRC cell line recently[ 69 ]. Thus, photopharmacology was achieved with a CRC cell line model system.…”
Section: Development Of Endoscopy Capable Of Handling Two-photon Illu...mentioning
confidence: 99%
“…Additionally, recent design efforts have been directed toward the development of NP systems that feature stimuli-responsive drug release; triggered by light, redox reactions, temperature, or pH; further enhancing spatial or temporal drug release [64][65][66][67][68]. pHresponsivity is particularly advantageous in the context of cancer treatment, as the tumor milieu exhibits a characteristically lower pH (6.5-7.2) than physiological pH (7.4) due to lactic acid production [69].…”
Section: Advantages Of Nanoparticle Drug Deliverymentioning
confidence: 99%
“…[5,6] Such photoswitchable drugs have been reported to target ion channels, [7] receptors, [8] and enzymes, [9] for treatment of diseases such as cancers [10,11] and bacterial infections. [12] Despite reports of numerous such photoswitchable drugs, [6,13] and also novel ways to deliver the required light source where and when required, [13,14] most reported exam-ples only show a modest two-to tenfold difference in biological activity between isomers. [6] More recent studies have reported compounds with a > 20-fold difference, [15] however still only a few reported photoswitchable drugs have been trialled in animal studies [13] and there are even fewer examples of human clinical trials.…”
Section: Introductionmentioning
confidence: 99%